Defining the work situation in organization theory: bringing Goffman back in. Issue 6 (2nd November 2022) - Klemsdal, Lars; Clegg, Stewart
ABSTRACT: The organization is traditionally assumed as the principal context of work. This assumption no longer holds in post-industrial and post-bureaucratic settings. Conducting meetings from home while juggling household responsibilities can be characterized as a form of organizing, but such contexts is not well accommodated by organizational perspectives. In such contexts, the organization plays a varying and often limited role. To accommodate this decomposition and re-composition of how work is organized, the present study develops a conceptual framework centered on the work situation . Building on Goffman's account of social situations (1966, 1974), the analysis draws an explicit distinction between the context of work as a series of potential frames and the work situation as an enacted framework for gestalting the specific work at hand. On this view, the organization as a formal setting or social assembly is just one of many frames that influence what actors do at work.